2004
DOI: 10.1080/10473289.2004.10470931
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Vehicle Emissions from an Attached Garage to Residential Indoor Air Pollution Levels

Abstract: The infiltration of vehicle emissions into a house from the attached garage was studied for 16 homes of differing designs using the same extensively characterized vehicle at each home. Before the in-home measurement program, the cold-start and hot-start tailpipe emissions and hotsoak evaporative emissions from a 1993 Buick Regal were measured using standard vehicle emissions measurement methods. The emissions were chemically characterized for methane, nonmethane hydrocarbons (NMHC), and carbonyl compounds. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 10 publications
0
23
0
3
Order By: Relevance
“…A number of studies have reported vehicles parked in attached garages as an important source of toxic organic compounds inside residences (Hawthorne et al 1986; Thomas et al 1993;Lansari et al 1996;Tsai and Weisel 2000;Mann et al 2001;Graham et al 2004;Dodson et al 2008). In addition to vehicles, people often store gasoline, yard, and garden supplies in garages, which can also be a source of volatile organic compounds (VOC, Batterman et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…A number of studies have reported vehicles parked in attached garages as an important source of toxic organic compounds inside residences (Hawthorne et al 1986; Thomas et al 1993;Lansari et al 1996;Tsai and Weisel 2000;Mann et al 2001;Graham et al 2004;Dodson et al 2008). In addition to vehicles, people often store gasoline, yard, and garden supplies in garages, which can also be a source of volatile organic compounds (VOC, Batterman et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…El aná li sis quí mi co se efec tuó en to dos los ca sos el mis mo día que se to ma ba la mues tra pa ra evi tar de grada ción del con te ni do. Res pec to al tiem po de du ra ción de to ma de mues tra, en la li te ra tu ra se ha ce re fe ren cia de un tiem po es ti mado de 250-300 se gun dos pa ra el ci clo de arran que en frío (Sin ger et al, 1999;Graham et al, 2004) en el cual los per fi les de emi sio nes co mien zan con pi cos agu dos de hidro car bu ros (HC) y CO, re sul ta do del ex ce so de combus ti ble pa ra la ig ni ción. Sin em bar go, es en un pe rio do de en tre 90-110 se gun dos pos te rior al mo men to mis mo del arran que don de se re gis tra la má xi ma emi sión acumu la da pa ra es te ti po de arran que (Graham et al, 2004).…”
Section: Meto Do Logía De Mues Treo Técnica De Mues Treounclassified
“…Res pec to a la lis ta de com pues tos iden ti fi ca dos en el aná li sis quí mi co, és ta se ge ne ró des pués de una re vi sión de los per fi les de emi sión que se ob tu vie ron en va rios es tudios rea li za dos tan to en Mé xi co co mo en otros paí ses (Mu gi ca et al, 2001;Ga mas et al, 1999;Ho et al, 1998;Sin ger et al, 1999;Graham et al, 2004). Ade más de es tas ca rac te ri za cio nes, tam bién se to ma ron en cuen ta los per files ob te ni dos en es tu dios de ai re am bien te en la Ciu dad de Mé xi co (Mu gi ca et al, 2003) y en otras re gio nes del or be (Mu ker jee et al, 2004;Thijs see et al, 1999).…”
Section: Análisis Químico De Las Mues Trasunclassified
See 1 more Smart Citation
“…For example, several homes in the BEAM study had attached garages, and it has been shown that this feature may affect indoor residential concentrations for certain compounds (Wallace, 1991;Gordon et al, 1999;Graham et al, 2004;Adgate et al, 2004b;Dodson et al, 2008). The influence of an attached garage was explored by calculating the three source indicators (namely, source strength, I-O difference and I/O ratio) for only those homes in the BEAM study without an attached garage, and then by comparing the across-study prediction results using these homes with the predictions based on all of the BEAM homes.…”
Section: Additional Influential Factorsmentioning
confidence: 99%